PENGARUH CORPORATE ENVIRONMENTAL PERFORMANCE DAN CORPORATE FINANCIAL PERFORMANCE TERHADAP PENGUNGKAPAN CSR PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (Research Institution and Community Service Wijaya Kusuma Surabaya University, 2013)
This study examined about corporate environmental performance and corporate financial performance for CSR disclosure because companies tend to give priority to financial performance to attract investors from the financial of the company. The purpose of this study is to determine the effect of corporate environmental performance and corporate financial performance for the CSR disclosure. Sample of this study were 13 companies listed in Indonesia Stock Exchange 2009-2011 and has ranked PROPER consistent during the study period. Techniques of data analysis done by hypothesis testing using multiple linear regression. The results showed that corporate environmental performance affect CSR disclosure. Meanwhile, corporate financial performance has no effect on CSR.